2018
DOI: 10.1007/s10549-017-4656-z
|View full text |Cite
|
Sign up to set email alerts
|

Circulating small-sized endothelial microparticles as predictors of clinical outcome after chemotherapy for breast cancer: an exploratory analysis

Abstract: Our results did not support sEMP as a marker of response to chemotherapy. However, our exploratory analysis suggests that in patients with metastatic breast cancer, the decrease of sEMP levels after chemotherapy is associated with better overall and disease free survival and might be superior to VEGFA levels as an angiogenesis-related prognostic marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…This might be explained by the additional presence of EMMPRIN on platelet-and immune cell-derived MV [11], which are directly influenced by the surgery. Prolonged high levels of total EV or endothelial cell-derived CD144+ MV after chemotherapy seem to predict a poor clinical response and were found to be associated with shorter progression-free and overall survival [134,135]. The same trend was observed in glioblastoma patients showing tumor progression after radiochemotherapy who generally exhibited higher MV levels compared with patients with pseudoprogression or stable disease [136].…”
Section: For Therapy Monitoringmentioning
confidence: 83%
“…This might be explained by the additional presence of EMMPRIN on platelet-and immune cell-derived MV [11], which are directly influenced by the surgery. Prolonged high levels of total EV or endothelial cell-derived CD144+ MV after chemotherapy seem to predict a poor clinical response and were found to be associated with shorter progression-free and overall survival [134,135]. The same trend was observed in glioblastoma patients showing tumor progression after radiochemotherapy who generally exhibited higher MV levels compared with patients with pseudoprogression or stable disease [136].…”
Section: For Therapy Monitoringmentioning
confidence: 83%
“…However, a research has shown that lower levels of ECs-derived microvesicles are related to better survival after chemotherapy in breast cancer patients, suggesting that ECs-derived exosomes also might have an important influence on tumor progression. 73 …”
Section: Exosome-mediated Metabolic Reprogramming In the Tmementioning
confidence: 99%
“…Aharon et al observed that microvesicles which bore MMP played a key role in angiogenesis and were involved in EC invasion and capillary formation (11). It is suggested that EMPs might be indicators of prognosis in patients with cancer (12,23). Consequently, the exact role of EMPs in cancer, and particularly in angiogenesis, needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%